The research and realization of wireless energy consumption detector based on the internet of things - Fu, W.; Shui, M.; Chen, Y.; Chen, L. (Journal of Digital Information Management, 2013)
Intelligent power consumption detection device is an important part in Smart Home system, which can intelligent identification , positioning , tracking, monitoring and management the household electrical parameters, enabling users to keep abreast of household electricity consumption. This paper is mainly about the design of a Wireless Energy Consumption Detector (WECD) based on the Internet of Things, combine with the IEEE802.15.4E wireless protocol. The whole system includes hardware and software parts, the choice of MCU chip, RF chip and power measurement chip for WECD, the design of each module circuit based on the chip working principle, the paper also make a key analysis of device driver module, wireless data forwarding module and wireless data showing module of indoor terminal. After a series of rigorous testing, the result indicates a high reliability and accuracy of the WECD.
Keywords: IEEE802.15.4E; Smart home; Wireless energy consumption detector